Restoration of Olfactory Memory in Drosophila Overexpressing Human Alzheimer’s Disease Associated Tau by Manipulation of L-Type Ca2+ Channels - Higham, James P.; Hidalgo, Sergio; Buhl, Edgar; Hodge, James J. L. (Frontiers in Cellular Neuroscience, 2019)
The cellular underpinnings of memory deficits in Alzheimer’s disease (AD) are poorly understood. We utilised the tractable neural circuits sub-serving memory in Drosophila to investigate the role of impaired Ca2+ handling in memory deficits caused by expression of human 0N4R isoform of tau which is associated with AD. Expression of tau in the entire mushroom body or parts of it as well as in mushroom body output neurons led to impaired memory. By using the Ca2+ reporter GCaMP6f, we observed changes in Ca2+ signalling when tau was expressed in these neurons, an effect that could be blocked by the L-type Ca2+ channel antagonist nimodipine or reversed by RNAi knock-down of the L-type channel gene. The L-type Ca2+ channel itself is required for memory formation, however, RNAi knock-down of the L-type Ca2+ channel in neurons overexpressing human tau resulted in flies whose memory is restored to levels equivalent to wild-type. Expression data suggest that Drosophila L-type Ca2+ channel mRNA levels are increased upon tau expression in neurons, thus contributing to the effects observed in memory and intracellular Ca2+ homeostasis. Together, our Ca2+ imaging and memory experiments suggest that expression of the 0N4R isoform of human tau increases the number or function of L-type Ca2+ channels in the membrane resulting in changes in neuronal excitability that can be ameliorated by RNAi knockdown or pharmacological blockade of L-type Ca2+ channels. This highlights a role of L-type Ca2+ channels in tauopathy and its potential therapeutic target for AD.